P-598 Dose accuracy of the follitropin-alfa, follitropin-alfa/lutropin-alfa and choriogonadotropin-alfa pen injectors used for fertility treatment. (30th June 2022) - Lispi, M; Cottell, E; Michalet, D; Araujo, T; Gleixner, R; D'Hooghe, T
Abstract: Study question: Do the Merck family of fertility pen injectors (follitropin-alfa, follitropin-alfa/lutropin-alfa, choriogonadotropin-alfa) meet the International Organization for Standardization (ISO 11608-1:2000/2012/2014) product-validation requirements? Summary answer: Each presentation of the family of fertility pen injectors performed as per the state-of-the-art product-validation specifications for dose accuracy in ISO 11608-1:2000/2012/2014 under atmospheric conditions. What is known already: Pen injectors for medically assisted reproduction must comply with ISO 11608-1:2000/2012/2014, which specifies essential performance requirements, including dose accuracy, and represent a benchmark for product reliability. Product-validation studies of the follitropin-alfa pen injector showed that three presentations (300 IU, 450 IU, and 900 IU) reliably dispensed accurate doses under a range of conditions, but no information was available for the follitropin-alfa/lutropin-alfa and choriogonadotropin-alfa pen injectors. This study was done to confirm that the incremental dose/clicks system was accurate for equivalence of volume (dose) delivered at standard atmospheric conditions for the complete Merck family of fertility pen injectors (follitropin-alfa, follitropin-alfa/lutropin-alfa, choriogonadotropin-alfa). Study design, size, duration: Laboratory-based dose accuracy measurement testing was carried out under standard atmospheric conditions, as specified in ISO 11608-1:2000/2012/2014, between 2015 and 2020. Participants/materials, setting, methods: Set doses (Vset) for three dose dial settings (minimum dose [Vmin], midpoint dose [Vmid] and maximum dose [Vmax] [follitropin-alfa, choriogonadotropin-alfa, and follitropin-alfa/lutropin-alfa]) or a single Vset (choriogonadotropin-alfa) were assessed, as appropriate. The last dose administered by the multi-dose device and cartridge and total extractable dose were assessed on the 900 IU and 300 IU follitropin-alfa and the 900 IU/450IU and 300/150 IU follitropin-alfa/lutropin-alfa-pen presentations. Sixty measurements per assessment were made for each Vset. Main results and the role of chance: Measurements were performed at two manufacturing sites. Dose accuracy tests for Vmin, Vmid and Vmax (dose dial settings of 12.5 IU, 87.5 IU and 150 IU, respectively, for the 150 IU pen [n = 2, 226 (one site)]; dose dial settings of 12.5 IU, 162.5 IU and 300 IU, respectively, for the 300 IU pen [n = 742 per site]; and dose dial settings of 12.5 IU, 237.5 IU and 450 IU, respectively, for the 450 IU [n = 180 per site] and 900 IU pens [n = 410 per site]) for the follitropin-alfa and the follitropin-alfa/lutropin-alfa pen injectors were within the acceptable limits defined in ISO 11608-1:2000/2012/2014. The results of further assessments of last dose and total extracted volume for each presentation of these devices were also within acceptable limits. Dose accuracy tests for the single use/single dose device classification (D1) of the choriogonadotropin-alfa pen injector (n = 210 [one site]) showed that the Vset (6, 500 IU) was within the acceptable limits according to ISO 11608-1:2000/2012/2014. Furthermore, dose accuracy tests for the single use/variable dose device classification (D2) of the choriogonadotropin-alfa pen injector (n = 180 [one site]) showed that the Vmin (260 IU), Vmid (3, 380 IU) and Vmax (6, 500 IU) values were also the within acceptable limits. Limitations, reasons for caution: These assessments were carried out by laboratory scientists, who are not the intended users of the pen injectors, and were not delivered into human tissue; therefore, although these conditions meet the international standards, they do not reflect the real-world use of the pen injectors by patients. Wider implications of the findings: The Merck family of fertility pen injectors functions reliably and the incremental dose/clicks system dispenses accurate doses, providing users with confidence that they can accurately administer the prescribed dose and minimize drug wastage outside of a clinic environment, which is more important than ever in light of the COVID pandemic. Trial registration number: not applicable